Типові сліди злочинів у сфері службової діяльності - Пчеліна, О. В.; Pchelina, O. V.; Пчеліна Оксана Василівна (Форум права. - 2017. - № 5. - С. 342–348, 2017)
Визначено, що типові сліди злочинів у сфері службової діяльності є важливим елементом відповідної криміналістичної характеристики, знання яких дозволяє вірно зорганізувати процес розслідування, зокрема збір доказів у кримінальному провадженні, за умов інформаційної недостатності. Виокремлено типові сліди злочинів у сфері службової діяльності.

It is shown that in forensic encyclopedic literature it is indicated that the term «trace» is used in the narrow and broad sense. In the first case, the trace are suggested to mean material-fixed reflection, and in the second – the result of any material change in the primary situation as a result of the commission of a crime. At the same time, the traces of the crime are nothing but a result of the reflection of the past, presented in the nowadays; sources of information, information for the knowledge of the crime. It is established that the trace of the crime is a collective concept, which includes the description of material and ideal maps and conditions that exist at the time of detection of the crime. It is suggested in this case to use the term «traces of a crime» in the broad sense and take this into account when identifying typical traces of crime in the field of official activity. Therefore, these crimes leave in the environment both material and ideal traces. In the article it is given the classification of documents as a source of evidence and an element of a trace pattern of crimes in the field of official activity – in content and in a form that does not claim to be exhaustive and can be supplemented taking into account the specifics of the sphere of operation of enterprises, institutions, organizations. It is concluded that typical traces of crime in the field of official activity are an important element of the relevant forensic characteristics. Their knowledge allows a person who conducts a pre-trial investigation of the specified category of criminal offenses, to correctly organize the investigation process, in particular, the gathering of evidence in criminal proceedings, in the event of information insufficiency.

Определено, что типичные следы преступлений в сфере служебной деятельности являются важным элементом соответствующей криминалистической характеристики, знание которых позволяет правильно организовать процесс расследования, в частности сбор доказательств в уголовном производстве, в условиях информационной недостаточности. Выделены типичные следы преступлений в сфере служебной деятельности.
Typical Traces of Crimes in the Field of Service Activity
Типичные следы преступлений в сфере служебной деятельности
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; типові сліди злочину; криміналістична характеристика злочинів; злочини у сфері службової діяльності; матеріальні сліди; ідеальні сліди; типичные следы преступления; криминалистическая характеристика преступлений; преступления в сфере служебной деятельности; материальные следы; идеальные следы; typical traces of a crime; forensic characteristic of crimes; crimes in the sphere of official activity; material traces; perfect traces